Supervisory control of concurrent systems - Iordache, Marian V; Antsaklis, Panos J (Boston : Springer, 2006)
Increasing complexity in engineering projects raises difficult challenges in industry and requires effective tools for correct-by-construction design or design verification. This book addresses the design of such tools for correct-by-construction synthesis of supervisors for systems and specifications represented in the discrete-event framework. The approach employed uses Petri nets as discrete-event models and structural methods for the synthesis of supervisors, and may lead to significant computational benefits. Highlighting recent progress in the design of supervisors by structural methods, the book represents a novel contribution to the field. One of the main features of the presentation is the demonstration that structural methods can address a variety of supervisor specifications under diverse supervision settings. The work is self-contained and includes necessary background on Petri nets and supervision. Requiring only basic knowledge of undergraduate-level discrete mathematics, the text is accessible to a broad audience. Researchers and developers from various engineering fields may find effective means to reduce the complexity of design problems in the discrete-event setting. Graduate students may use the work as a self-study reference, and portions of the text may be used in advanced courses on discrete-event systems.
Includes bibliographical references (p. 265-278) and index.
Keywords: Petri net theory; Discrete event systems; Structural methods for supervisor synthesis; Correct-by-construction design; Applications and case studies